Motif Sosial Penggunaan Sneakers sebagai Identitas Diri - Rakan Qabus, Benito; Ana Fitriana Poerana; Fajar Hariyanto (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze how social motives, including motives (past experiences) and to motive (social and psychological goals), influence the use of sneakers as a form of self-identity in urban communities in South Jakarta. The research method uses a qualitative approach with Alfred Schutz's phenomenological design. Data was collected through in-depth interviews, participant observation, and documentation of informants who are active sneaker users in the Blok M, Cipete, and Fatmawati areas, using purposive and snowball sampling techniques. Data analysis was conducted using the interactive model of Miles and Huberman. The results show that motive is formed from past emotional experiences, social environmental influences, and first experiences using branded sneakers that shape preferences and consumption habits. Meanwhile, to motive is driven by the desire to gain social recognition, build self-image, and be accepted in the community. These two motives interact in shaping the meaning of using sneakers as a symbol of self-identity. The conclusion of this study confirms that sneakers are no longer merely a functional necessity, but rather a symbolic communication medium in building social identity. This study contributes to the development of the phenomenology of consumption by emphasizing the relevance of Schutz's theory in understanding contemporary urban consumption culture. Keywords: Because of motive, to motive, Phenomenology, Sneakers, Social Identity, Urban